Realization of neutral white light emission in CaMoO4:4Dy3+ phosphor via Sm3+co-doping - Dixit P.; Chauhan V.; Rai S.B.; Pandey P.C. (My University, 2025)
In this paper, Dy3+/Sm3+ co-doped CaMoO4 compounds were synthesized successfully via the auto-combustion method. The tetragonal crystal structure of the phosphors is confirmed by structural study. The vibrational modes are examined by infrared spectroscopy. It has been observed that 4% Dy3+ doped CaMoO4 phosphor shows maximum luminescence intensity. Further, Sm3+ ions are co-doped in 4% Dy3+ doped CaMoO4 for improving their luminescence properties. The Photoluminescence study illustrates energy transfer between [MoO4]−2 groups and Dy3+/Sm3+ ions, under 296 nm excitation. The Dy3+ doped CaMoO4 phosphors emit two sharp peaks at 484 nm (4F9/2→6H15/2) and 574 nm (4F9/2→6H13/2). Further, with Sm3+ co-doping in 4% Dy3+ doped CaMoO4 phosphor, another distinctive emission peak is observed at 647 nm, which is attributed to 4G5/2→6H9/2 electric dipole transition of Sm3+ ion. The Dy3+/Sm3+ co-doped CaMoO4 phosphor gives overall white light emission. For 3% Sm3+ co-doped CaMoO4:4Dy3+ phosphor, white light is obtained with the CCT value of 4439 K. Hence, the prepared phosphor might be used in white lighting diode applications. © 2021 Elsevier B.V.